ANALISIS PENGELOLAAN AGROFORESTRI TRADISIONAL PADA MASYARAKAT DESA PARADUAN KECAMATAN RONGGURNIHUTA KABUPATEN SAMOSIR - Irawati Samosir; Hafizianor -; Ahmad Yamani (Jurnal Sylva Scienteae, 2021)
Agroforestry management is land management by combining forestry crops with agricultural crops or animals (livestock) in ecologically, socially and economically sustainable systems. Agroforestry in Paraduan Village is a traditional agroforestry. This research The purpose of this research is to examine the traditional agroforestry patterns applied by the community and analyze the traditional agroforestry management system applied by the people of Paraduan Village Ronggurnihuta sub-district of Samosir Regency. Repondent determination is done by taking purposive sampling method (example) against households that carry out the management of traditional agroforestry, namely households that own land that is as many as 40 respondents. The stratification of the land ownership of the village community as a sample is divided into 4 patterns namely agrisilviculture, silvopastura, agrosilvastura and silvofishery. Data and information collection methods are carried out using various approaches according to research needs, namely literature studies, interviews and field observations. Agroforestry plants grown in one land are grouped into forestry crops namely Pinus, Suren, Ares, Jati, Mahoni, Kemiri grown on the edge of the land, agricultural crops namely Coffee plant, Onion, Chili, Chocolate, Ginger, Corn, Beans, Bananas, Rias, Betel, Dutch Eggplant, Turmeric, Cassava, farm animals that are raised are Cows, Buffaloes, Chickens village And Pigs,  in the fishery sector are Catfish and Mujair. The management system implemented by Paraduan villagers is a traditional system with manual management using roughing tools and seeds available with a management system starting from soil management and seed procurement, Planting, Maintenance, Eradication of pests, Harvesting and marketing.Keywords: Agroforestry Patterns; Management; Land processing